Agreement of actors in the dairy chain for the non-deforestation of forests and the non-transformation of the páramo - CGIAR Research Program on Water, Land and Ecosystems (2021)
The WLE/Sustainable Land Use Systems project coordinates government-led agreement on zero deforestation in the dairy value chain. In 2021 it engaged new partners and contributed to national livestock actor dialogues.